Dynamics of Middle School Teacher Performance: Analysis of the Influence of Transformational Leadership, School Culture and Motivation in Gido District, Nias Regency - Samselinar Lase; Rosmala Dewi; Ibnu Hajar (Randwick International of Education and Linguistics Science Journal, 2024)
The aim of this research is to determine the influence of transformational leadership, school culture, and motivation on teacher performance. The problem with this research is that teacher performance results are still low in planning, implementing, and evaluating learning. This research was carried out in public and private junior high schools in Gido District, Nias Regency. The population of this research was 142 people, and the research sample was 106 people. The research method is ex post facto, with path analysis techniques. The research results found were: (1) transformational leadership has a direct positive effect on teacher performance; (2) transformational leadership has no direct positive effect on teacher motivation; (3) school culture has a direct positive effect on teacher performance; (4) school culture has a direct positive effect on teacher motivation; (5) motivation has a direct positive effect on teacher performance; (6) the principal's leadership has a direct positive effect on performance through motivation; and (7) school culture has a direct positive effect on performance through motivation. Based on the results of this research, it can be concluded that transformational leadership and school culture have a significant effect on increasing teacher motivation, and transformational leadership and school culture have a significant effect on increasing teacher performance in planning, implementing, and evaluating learning.